The Relationship Between Mallampati Score And Obesity With the Risk of OSAHS in Down Syndrome Children - Uni Gamayani; Agnes Christine Yolanda Sihite; Iin Pusparini; Nushrotul Lailiyya (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2022)
Obstructive Sleep Apnea/Hypopnea Syndrome (OSAHS) has commonly occured in Down syndrome children caused by the abnormalities in upper respiratory tract anatomy and obesity. This study aims to identify the correlation between Mallampati score and obesity and the risk of OSAHS in Down syndrome children. This was an analytical descriptive cross-sectional study. This study was conducted in children with Down syndrome from September until November 2017. All parents filled the Indonesian Pediatric Sleep Questionnaire (PSQ), then all of the children were examined for Mallampati score and BMI. The correlation was analyzed by the Pearson Chi-Square model. Thirty-six subjects were included in this study. The number of male subjects were slightly more (61.1%), the mean age of the subjects was 8.42±4,449 years, with 52.8% (19 subjects) having OSAHS. There were 23 subjects (63.9%) who had Mallampati scores of 3 and 4, with 13 subjects (36.1%) were obese. This study concluded a statistically significant correlation between Mallampati score and obesity and the risk of OSAHS in Down syndrome children (p-value 0.001 and 0.029). Mallampati score and obesity had a significant correlation with the risk of OSAHS in Down syndrome children.